ESTUDO DA ADOÇÃO INDIVIDUAL DA REDE SOCIAL PROFISSIONAL LINKEDIN - Camargo, Lilian Cristina Carvalho (2015)
The turnover intention refers to the probability of individuals leaving their current job. This topic has become relevant to organizations since it is a potential problem, which may affect the organizations competitiveness, amongst other reasons. It is believed that some of the individuals who have turnover intention look for means of communication, new technologies, such as the professional social network LinkedIn, in order to spread their professional information, find professional opportunities by networking, as well as obtain more information about the labor market, besides different other functions. Therefore, the turnover intention may be considered as a previous factor to the individual adoption of the professional social network LinkedIn. This study has analyzed the previous factors that may influence the usage and how they use the professional social network LinkedIn, guided by the theoretical perspective of the Unified Theory of Acceptance and Use of Technology (UTAUT), by Venkatesh et al (2003), and also guided by the scale of the turnover intention, by Siqueira et al (2014)and Van Dam (2008). The research is based on a quantitative investigation approach, in which data collection was done using a research tool, and obtained 292 answered questionnaires, which has made it possible to validate the relations between the constructs of the research model developed for the study of the individual adoption of the professional social network LinkedIn. There was an analysis of structural equations to make the test of the study hypotheses, based on PLS-PM (Partial Least Squares Path Modeling) from which satisfactory measures for all the investigated constructs and proposed models were presented, and all the relations between the constructs were significant. The results obtained by this study confirm the influence of previous factors, such as Performance Expectancy, Effort Expectancy, Social Influence, and Turnover Intention, on the intention of using the professional social network LinkedIn. The study concludes that the Performance Expectancy was revealed to be the greatest influence in the intention of using LinkedIn, since there is the perception that by using it, it is possible to obtain some professional benefits as well as other aspects. The second factor to present the greatest influence was the Turnover Intention, once some individuals, by adopting LinkedIn, may tend to show it to other people or organizations that are interested in their talents, experiences, skills, network and so on. The Effort Expectancy, in turn, showed that some individuals notice it is easy to interact with such technology, and the Social Influence showed that there is the individuals perception as to the influence of their network in their intention of using LinkedIn.